COVER AND PREFACE JURNAL KONVERSI ENERGI DAN MANUFAKTUR VOL. 7 NO. 2 (2022) - Jurnal Konversi Energi dan Manufaktur Editor's (Universitas Negeri Jakarta, 2022)
Rohmatin et al., in their paper, discuss forklift performance analysis, where this paper aims to find out whether forklift performance is still within the standards set by using the overall equipment effectiveness (OEE) method. Syaefudin et al., in their paper, analyze the calculation of the control and power design of portable Senai tools to get the appropriate power requirements in the field. Syaka et al., in their paper, conducted an experimental study of the performance of an air compression engine with modified centric gear on 4-stroke internal combustion, which was changed to 2-stroke by modifying the centric gear ratio from 2:1 to 1:1. Syamsuir, in their paper, carried out the electroplating process of copper and nickel to know the effect of the layer formed on Ms 7210 low carbon steel on the corrosion rate. Susetyo et al., in their paper, discuss the design and testing of cutting support devices with a rectifier rail system for plasma cutting operations. Fikri et al., in their paper, conducted research in the field of welding to know the effect of current strength on penetration depth, welding width, and hardness in the heat-affected zone (HAZ) of ST-37 steel. Wulandari and Dhiyaulhaq, in their paper, reviewed articles with a discussion on the use of exhaust heat from several transportation methods to cool cabins or products through conceptual research by reviewing related literature. Hartono et al., in their paper, designed a rice planter using the jajar legowo system, which has an optimal axle and finned wheel design.